Venoarterial Extracorporeal Membrane Oxygenation After Surgical Repair of Type A Aortic Dissection - Mariscalco, Giovanni; Fiore, Antonio; Ragnarsson, Sigurdur; El-Dean, Zein; Jónsson, Kristján; Dalén, Magnus; Fux, Thomas; Ruggieri, Vito G; Gatti, Giuseppe; Juvonen, Tatu; Zipfel, Svante; Dell'Aquila, Angelo M; et al. (The American journal of cardiology, 2020)
Venoarterial (VA) extracorporeal membrane oxygenation (ECMO) support for postcardiotomy cardiogenic shock (PCS) in patients undergoing surgery for acute type A aortic dissection (TAAD) is controversial and the available evidence is confined to limited case series. We aimed to evaluate the impact of this salvage therapy in this patient population. Between January 2010 and March 2018, all TAAD patients receiving VA-ECMO for PCS were retrieved from the PC-ECMO registry. Hospital mortality and other secondary outcomes were compared with PCS patients undergoing surgery for other cardiac pathologies and treated with VA-ECMO. Among the 781 patients in the PC-ECMO registry, 62 (7.9%) underwent TAAD repair and required VA-ECMO support for PCS. In-hospital mortality accounted for 46 (74.2%) patients, while 23 (37.1%) were successfully weaned from VA-ECMO. No significant differences were observed between the TAAD and non-TAAD cohorts with reference to in-hospital mortality (74.2% vs 63.4%, p = 0.089). However, patients in the TAAD group had a higher rate of neurological events (33.9% vs 17.6%, p = 0.002), but similar rates of reoperation for bleeding/tamponade (48.4% vs 41.5%, p = 0.29), transfusion of ≥10 red blood cell units (77.4% vs 69.5%, p = 0.19), new-onset dialysis (56.7% vs 53.1%, p = 0.56), and other secondary outcomes. VA-ECMO provides a valid support for patients affected by PCS after surgery for TAAD.
Keywords: Extracorporeal Membrane Oxygenation; záchranná terapie; lidé; Middle Aged; Adult; pooperační komplikace; registrace; délka operace; Female; disekce aorty; Humans; Postoperative Complications; Aortic Dissection; Operative Time; Registries; Hospital Mortality; lidé středního věku; mužské pohlaví; Salvage Therapy; ženské pohlaví; Male; Aged; mimotělní membránová oxygenace; dospělí; mortalita v nemocnicích; senioři